ANALYSIS OF SUSTAINABILITY OF SMALL-SCALE CAPTURE FISHERIES IN BANGKO DISTRICT, ROKAN HILIR DISTRICT - Darwis, Darwis; Arief, Hazmi; Siahaan, Neti Gebriella; Nasution, Tio Afandi (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Riau, 2025)
This research was conducted in Bangko District, Rokan Hilir Regency, Riau Province. This research aims to analyse the sustainability status of small-scale capture fisheries and leverage attributes that support their sustainability in the future. The method used in this research is a survey method with a quantitative approach and the determination of respondents is carried out randomly purposive sampling with the consideration that the respondents taken were two fishermen group leaders, one community leader, one fisheries instructor, one academic, one village official, two people from the Fisheries and Maritime Service, and one fishermen cooperative. The public criteria selected in this study to collect the primary data were seven people, namely, fishermen. The number of public respondents selected came from villages/districts, so the total number of respondents was 16. Based on research results sustainability status small-scale capture fisheries show a sustainability index with an average value of 51.65 or in the range 50-75 which is classified as quite sustainable and the leverage attributes from the five dimensions that are the most sensitive and have high leverage in influencing the sustainability status of capture fisheries include fishing time, nature ownership of fishing facilities, type or nature of fishing gear, fishermen's education level, and fisheries management plan (RPP).